2021
DOI: 10.9734/jamb/2021/v21i1030394
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality Assessment and Identification of Antibiotic Resistant Bacteria at Different Stages of the Milk Supply Chain in Dhaka City of Bangladesh

Abstract: Aims: Milk works as an excellent medium for bacterial growth and can turn into a fatal source of food borne diseases when consumed without pasteurization. This study was carried out to examine the microbiological quality of milk from three different points of milk supply chain to investigate whether the dairy stakeholders are maintaining the consumer safety or not. Study Design: A cross sectional study Place and Duration: The study took place at the Food Microbiology lab of Institute of Nutrition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The count of viable cells present in the samples was determined using the provided formula given by Nowar et al (2021) (Nowar et al, 2021). Colonies were selectively isolated and preserved on nutrient agar slants.…”
Section: Enumeration Of Total Bacterial Count (Tbc) and Total Colifor...mentioning
confidence: 99%
See 1 more Smart Citation
“…The count of viable cells present in the samples was determined using the provided formula given by Nowar et al (2021) (Nowar et al, 2021). Colonies were selectively isolated and preserved on nutrient agar slants.…”
Section: Enumeration Of Total Bacterial Count (Tbc) and Total Colifor...mentioning
confidence: 99%
“…A study conducted in Ethiopia in 2018 reported a range of total bacterial counts, ranging from 5x10 3 to 3.18x10 8 CFU/mL in raw milk and 4.4x10 1 to 4.43x10 5 CFU/mL in pasteurized milk samples (Tamirat, 2018). The consumption of such inadequately pasteurized milk not only leads to foodborne illnesses but also raises the risk of consuming multi-drugresistant bacteria (Nowar et al, 2021). Global public health faces a significant threat from the proliferation of multidrug-resistant (MDR) microorganisms (Hassani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%